Addendum to "Generalized radiative transfer theory for scattering by particles in an absorbing gas: Addressing both spatial and spectral integration in multi-angle remote sensing of optically thin aerosol layers" [J. Quant. Spectrosc. Radiat. Transfer 205 (2018) 148–162]. (February 2018) - Davis, Anthony B.; Xu, Feng; Diner, David J.
Highlights: The steps to derive the generalized 1D radiative transfer equation (RTE) from its standard 3D counterpart are clarified. The steps required to go from standard monochromatic 1D RTE to its generalized counterpart for accelerated spectral integration in the presence of scattering are simpler. Error quantification is used to validate the spectroscopic application of generalized radiative transfer directly from its first principles. Abstract: This addendum supplements the paper identified in the title.